Prehospital Pericardiocentesis Using a Pneumothorax Needle. (4th May 2022) - Robinson, Aaron E.; Jones, Gregg A.; Nystrom, Paul C.; Stirling, Adam; Vanderbosch, Kelsey; Simpson, Nicholas S.
Abstract: Case: We discuss a patient with a penetrating knife wound to the chest who lost pulses from cardiac tamponade. Prehospital ultrasound was able to quickly identify the tamponade and a pericardiocentesis was performed using a Simplified Pneumothorax Emergency Air Release (SPEARTM) Needle (North American Rescue, LLC, USA) with subsequent return of spontaneous circulation. Discussion: Penetrating chest trauma carries significant morbidity and mortality. In traumatic cardiac arrest due to a penetrating mechanism, it is paramount that the patient be transported to a trauma center as quickly as possible. Prehospital pericardiocentesis is a potential life-saving intervention.